Rail transport corridors in the CAREC region: Long-term supply chain resilience and short-term shocks - Richard Pomfret (Asian Development Bank Institute (ADBI), 2023)
International supply chains are dependent on ease of crossing borders and efficient connectivity in terms of price, speed, and reliability. Initially responding to demand from automobile and electronics firms to connect their European and Chinese supply chains with faster and more reliable freight services than maritime shipping, the Eurasian rail transport corridor was established in the 2010s. The rail Landbridge was resilient through deteriorating EU-Russian Federation relations after 2014 and the 2020-2021 COVID-19 epidemic. However, following the Russian invasion of Ukraine and inclusion of the Russian rail company in western sanctions in February 2022, traffic growth along the main Landbridge routes stalled. This paper analyzes the response of supply chain managers in 2022-2023 to the sanctions, and the role of public policy in creating reliable alternative routes. Diversification and strengthening of Eurasian rail corridors benefit Central Asia Regional Economic Cooperation (CAREC) members through revenues from transit fees. More important is the reduction in transport costs for trade among CAREC members and with other countries, which can support economic strategies aimed at economic diversification.
Keywords: F13; 330; supply chains; connectivity; Eurasia; Landbridge